Doing right - Hebert, phillip 1961- (canada mixed sources, 2009)
Puzzling over conflicting advice from family members, seventeen-year-old DeQuin Lewis continually faces trouble in his St. Paul, Minnesota, neighborhood, until a betrayal leads him to fresh start in an alternative school, one confrontation away from losing everything.
Keywords: Conduct of life -- Fiction; African Americans -- Fiction; Prisoners' families -- Fiction; Fathers and sons -- Fiction; Uncles -- Fiction; Grandfathers -- Fiction; Saint Paul (Minn.) -- Fiction